Two-Pore K(+) channels, NO and Metabolic Inhibition - Lu, Zhongju (2007)
Ischemic preconditioning is a potent endogenous mechanism protecting many organs from the devastating effects of prolonged ischemia. In the heart, NO is one mediator of this myoprotective response thought to involve activation of the K(ATP) channel. Ischemic preconditioning is known to be induced by metabolic inhibition using sodium cyanide (NaCN) in single cardiomyocytes. In the present study we show for the first time that the end effector channel activated by NaCN has been incorrectly identified. The channel activated is not K(ATP) but instead belongs to the relatively new family of two-pore domain potassium channels (K2P). Further when activated by metabolic ischemia, the amplitude of K2P current is directly modulated by activators and inhibitors of the NO pathway.